Long-term Assessment of Healthcare Utilization 5 Years After Respiratory Syncytial Virus Infection in US Infants. (4th June 2019) - Simões, Eric A F; Chirikov, Viktor; Botteman, Marc; Kwon, Youngmin; Kuznik, Andreas
Abstract: Background: Respiratory syncytial virus (RSV) is the primary cause of respiratory tract infections in infants; however, current burden estimates report only the short-term effects of acute infection. Methods: Infants with RSV infection and ≥24 months of continuous enrollment were retrospectively identified from the Truven MarketScan database (1 January 2004–30 September 2015). Exposed infants (n = 38 473) were propensity score matched to nonexposed controls (n = 76 825) by baseline characteristics and gestational age. Five-year cumulative all-cause, asthma/wheezing, and respiratory event–related hospitalization rates and physician and emergency department healthcare-resource utilization rates were assessed. Results: During follow-up, RSV-infected cohorts had higher average all-cause cumulative hospitalization rates, compared with controls, with values of 79.9 hospitalizations/100 patient-years (95% confidence interval [CI], 41.7–118.2) for 213 early premature infants ( P < .001), 18.2 hospitalizations/100 patient-years (95% CI, .8–35.7) for 397 premature infants ( P = .04), 34.2 hospitalizations/100 patient-years (95% CI, 29.1–39.2) for 4446 late premature infants ( P < .001), and 16.1 hospitalizations/100 patient-years (95% CI, 14.9–17.4) for 33 417 full-term infants ( P < .001). Cumulative rates of physician and emergency department visits were also higher for RSV-infected infants. Asthma/wheezing accounted for 10%–18% of total 5-year physician visits. Conclusions: Infant RSV infection has a significant long-term healthcare-resource utilization impact across gestational ages for at least 5 years after infection, most of it in the first 2 years. Systematically collecting healthcare-resource utilization data will be important for cost-effectiveness evaluations of RSV interventions in planned or ongoing trials. Abstract : Respiratory syncytial virus (RSV) infection in infancy has significant burden for ≥5 years, affecting all gestational ages and categories of healthcare utilization beyond the acute infection. Systematically collecting healthcare utilization data is important for evaluations of RSV interventions examined in planned or ongoing trials.